2018
DOI: 10.3390/rs10040595
|View full text |Cite
|
Sign up to set email alerts
|

Lake Area Changes and Their Influence on Factors in Arid and Semi-Arid Regions along the Silk Road

Abstract: Abstract:In the context of global warming, the changes in major lakes and their responses to the influence factors in arid and semi-arid regions along the Silk Road are especially important for the sustainable development of local water resources. In this study, the areas of 24 lakes were extracted using MODIS NDVI data, and their spatial-temporal characteristics were analyzed. In addition, the relationship between lake areas and the influence factors, including air temperature, precipitation, evapotranspirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 39 publications
(35 reference statements)
0
43
0
Order By: Relevance
“…Therefore, there are only two drought periods in our research, and future studies with more data can provide a better understanding of the relationship between seasonal indicators and drought periodicity in longer period. Secondly, insufficient effects of human activities on surface water and phenology were examined in this study, but agricultural activities such as irrigation and multiple growth seasons were excluded, especially in drought periods [85,86]. For example, the dryer the condition, the more water is pumped from rivers and lakes for irrigation, which reduces SWA from observation.…”
Section: Limitation and Future Researchmentioning
confidence: 99%
“…Therefore, there are only two drought periods in our research, and future studies with more data can provide a better understanding of the relationship between seasonal indicators and drought periodicity in longer period. Secondly, insufficient effects of human activities on surface water and phenology were examined in this study, but agricultural activities such as irrigation and multiple growth seasons were excluded, especially in drought periods [85,86]. For example, the dryer the condition, the more water is pumped from rivers and lakes for irrigation, which reduces SWA from observation.…”
Section: Limitation and Future Researchmentioning
confidence: 99%
“…In addition, a rapid reduction was noticed in the surface area of the lake between 1972 and 1984. Tan et al (2018) analysed areal changes of 24 lakes along the Silk Road from China to Europe. Authors indicated that surface areas of 15 lakes had decreased while areas of 9 lakes had increased from 2001 to 2016.…”
Section: Figure 2 Temporal Change In Water Surface Areamentioning
confidence: 99%
“…Monitoring of spatial and temporal changes using satellite images has globally become crucial for better understanding and explaining of environmental changes in the reservoirs. Spatial and temporal changes of water surface in lakes and reservoirs were monitored by several scientists (Sidle et al, 2007;El-Asmar et al, 2013;Abu-Faraj et al, 2014;Hossen et al, 2018;Ji et al, 2018;Tan et al, 2018;Yapiyev et al, 2019). There are few researches on change monitoring of water surface in lakes and reservoirs in Turkey (Akar et al, 2002;Reis and Yılmaz, 2008;Durduran, 2010;Avdan et al, 2013;Bahadır, 2013;Battal et al, 2016;Erener et al, 2016;Yücel and Turan, 2016;Sarp and Ozcelik, 2017;Topuz and Karabulut, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Change rate and change range were used to estimate regional tendency based on the linear regression and appeared to be unaffected by possible constant biases present in the data [20,27,[31][32][33]. Therefore, the slope and range were used to assess the interannual variations of LST and SINDVI [20,31,33]. The slope represents the change rate of each pixel calculated by the ordinary least-squares estimation via linear regression from 2001 to 2016.…”
Section: Time-series Analysismentioning
confidence: 99%